Tinjauan Hukum Strategi Optimalisasi Kebijakan untuk Mengatasi Tantangan Dalam Pengelolaan Limbah Padat Medis - Said, Feriany; Wulandari, Christine; Bakri, Samsul; Sukohar, Asep; Sumekar, Diyah (Universitas Sang Bumi Ruwa Jurai, 2024)
Solid medical waste management is a crucial issue in the health system. RSUD Menggala of Tulang Bawang Regency is responsible for ensuring orderly and efficient waste management. However, challenges in solid medical waste management often arise, including limited resources and policy changes. A qualitative approach was used as a way to conduct descriptive research, and it was found that Menggala Regional Hospital has not fully complied with regulations according to Permenkes RI Number 7 of 2019 concerning Hospital Environment. Some optimisation strategies that can be proposed include increasing awareness, strengthening resources, strict supervision, external cooperation, and increasing HR capacity. With the right steps, RSUD Menggala can ensure regulatory compliance, reduce environmental risks, and improve patient and health worker safety. This research serves as a basis for RSUD Menggala in formulating more effective policies in solid medical waste management